Giant Recurrence Pituitary Adenoma After Three Times Transphenoidal Removal Surgery, One Craniotomy Procedure, and 30 Doses of External Radiotherapy - Laurentius Aswin Pramono; Em Yunir; Tri Juli Edi Tarigan; Syntia Nusanti; Renindra A Aman; Indrati Suroyo (Acta Medica Indonesiana, 2021)
This is a case of 42nd year-old woman with history of sight loss in her both eyes. She experienced headache and visual field decrease gradually since 2014. After several laboratory and imaging examinations, from her dynamic pituitary magnetic resonance imaging (MRI), it is concluded that she had a giant adenoma of the pituitary gland which compressed to her optic chiasm. From her pituitary laboratory hormone panel, it is revealed that the tumor is a non-functioning pituitary adenoma. From the neuro-ophthalmology (campimetry) examinations, she had papillae atrophy in her both eyes and also bilateral temporal hemianopia.